Understanding morphology - Haspelmath, Martin; Sims, Andrea D. (New York : Routledge, 2023)
This introduction to morphology assumes no prior knowledge of linguistics and presents the field of morphology in an accessible way. Emphasis is put on presenting a range of morphological phenomena from a wide variety of languages.
Previous ed.: London : Arnold, 2002.
Keywords: Grammar, Comparative and general -- Morphology